Requisite skill differences of baccalaureate graduates among three building disciplines - Weber, Paul A., author; Jansen, Duane S., advisor; Hauck, Allan J., advisor; Gloeckner, Gene W., committee member; Daly, Joseph L., committee member; Murphy, John, committee member (Colorado State University. Libraries, 2000)
The traditional project delivery system of design-bid-build is being overtaken by an alternative delivery system called design build. Design build is actually a reemerging discipline dating back to the "master builders" of the renaissance. Design build attempts to, again, blend the two disciplines of design and construction into a single source method of procurement. The purpose of this study was to explore the differences among architects, constructors, and design builders, in the requisite skills they seek in graduates of design and construction management programs. The literature review recognized skill sets identified by the architecture and construction management disciplines, however, no skill sets were found unique for design builders. A methodology was developed to determine if differences exist among architects, constructors, and design builders. A mailed questionnaire was sent to 108 architects, 108 constructors, and 108 design builders utilizing a questionnaire containing 32 questions relating to three broad skill sets: (a) architecture skills, (b) construction management skills, and (c) general business skills. One hundred and eighty sets of data were obtained yielding a 56 percent response rate. An alpha level of .05 was used in making decisions relative to the statistical significance of the results. The results of this study utilizing analysis of variance and post hoc tests showed a statistically significant difference among the professions relating to the three broad skill sets studied. The data indicated design builders were more similar to constructors than to architects in the skills they seek in graduates. However, design builders valued abilities relating to entrepreneurial skills and marketing skills over that of constructors and architects. All three groups rated problem solving, verbal communication skills, and effectiveness in working relationships as being very important. It was suggested that construction management programs, with modifications, would be best suited to provide the set of skills sought by design builders in baccalaureate graduates.
Keywords: civil engineering; skills; college graduates; studies; design; building codes; variance analysis